Heroisme i sten? Arkitektur, ny kunst og ideologi på Gymnastikhøjskolen i Ollerup - Bonde, Hans (Forum for Idræt, 2013)
Heroism in Stone? Architecture, New Art and Ideology at the Gymnastics Academy in Ollerup In the period from 1920 to 1926 the internationally renowned gymnastics pedagogue, Niels Bukh, created a huge neoclassical inspired sports complex that completely broke with the dimensions of the small South Funen village of Ollerup. In 2007, a donation from the New Carlsberg Foundation opened up for the introduction of new artworks on the gymnastics school. The artists argued that Bukh’s “heroism” demanded an aesthetic counterpart. The article follows two main tracks: 1) Do the original art and architecture of Bukh’s gymnastics high school express authoritarian-heroic traits? 2) Can the new art on Ollerup be said to create a response to such alleged heroic aspects? The conclusion is that the traditional architecture and art at Ollerup contain only vague and tentative signs of “heroism.” The new artists that attempt to create a counterweight to Bukh heroism lands in the paradox that they themselves have built a much more faceless and soaring art than Bukh and his democratically oriented architect, Ejnar Mindedal, had originally established. At the same time, the new artists have moved around with statues and sculptures in such a way that the school’s fine sexual-aesthetic axis opposing feminine and masculine, heterosexual and homosexual, and internal and external, have been lost.